2008
DOI: 10.1002/ppul.20900
|View full text |Cite
|
Sign up to set email alerts
|

Wilson–Mikity syndrome: Updated diagnostic criteria based on nine cases and a review of the literature

Abstract: WMS is a rare but clearly identifiable syndrome with significant morbidity, predominantly affecting infants below 1,500 g birth weight. The earliest pathology appears to be alveolar air leak. Inflammatory activation induced by cystic interstitial air may cause the subsequent progressive respiratory disease. Management is supportive but should include investigation for pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Relatively large case series reports of WMS with bubbly/cystic appearance were published in North America in the 1960s: 22 cases by Swyer et al 33 and 34 cases by Hodgman et al 15. Recently, nine cases of WMS were reported by Hoepker et al from the Canadian NICU 34. Exact percentages of WMS in the above case series reports are unknown because of a limited description of their prevalence.…”
Section: Discussionmentioning
confidence: 96%
“…Relatively large case series reports of WMS with bubbly/cystic appearance were published in North America in the 1960s: 22 cases by Swyer et al 33 and 34 cases by Hodgman et al 15. Recently, nine cases of WMS were reported by Hoepker et al from the Canadian NICU 34. Exact percentages of WMS in the above case series reports are unknown because of a limited description of their prevalence.…”
Section: Discussionmentioning
confidence: 96%
“…The present disease course suggests that infants diagnosed with WMS have persistently reduced lung function, which is predominantly obstructive in nature, and are at risk of progressing to a COPD‐like phenotype later in life. The present patient developed characteristic clinical features of WMS, such as evidence of apparent intrauterine inflammation, lack of RDS despite premature birth, and bubbly/cystic emphysematous lung changes in the early neonatal period, despite minimal respiratory support …”
Section: Discussionmentioning
confidence: 70%
“…A recent cohort study of extremely low‐birthweight survivors in Japan reported that a bubbly and cystic appearance of the lungs in the neonatal period, which is associated with immaturity and intrauterine inflammation, was the strongest determinant of impaired lung function at school age, particularly forced expiratory volume in 1 s/forced vital capacity ratio, indicating an obstructive lung disorder . Immaturity and absence of RDS, which are background characteristics in the bubbly and cystic appearance group, are similar to the symptoms observed in WMS …”
Section: Wilson–mikity Syndrome In Japanmentioning
confidence: 69%
“…After 50 years of progress in neonatal medicine, the current position of WMS in the spectrum of newborn lung disease is unclear. Apart from occasional case reports, it is now rarely mentioned and is commonly considered an anachronism or to have been lost within the broadening diagnostic range of CLD (Fig. ) .…”
Section: History Of Wilson–mikity Syndromementioning
confidence: 99%